2022
DOI: 10.1039/d2qi01168a
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Ru oxidation within electrospun carbon nanofibers to boost hydrogen and oxygen evolution for electrochemical overall water splitting

Abstract: Developing bifunctional high-efficiency electrocatalysts with prominent durability toward overall water splitting is a fascinating way to produce hydrogen for clean energy application. In this work, partially oxidized Ru nanoparticles integrated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Notably, recent work showed that a combination of metallic and partially oxidized Ru nanoparticles is beneficial for overall water splitting reactions including the HER. 35 Therefore, it is reasonable to expect that the presence of both metallic and oxidized Re would be valuable to enhance the catalytic activity of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, recent work showed that a combination of metallic and partially oxidized Ru nanoparticles is beneficial for overall water splitting reactions including the HER. 35 Therefore, it is reasonable to expect that the presence of both metallic and oxidized Re would be valuable to enhance the catalytic activity of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Preferably, a very low overpotential as well as significantly less Tafel slopes were needed for effective HER performance. [ 25 ] The HER performance of the electrode was characterized by LSV at a scan rate of 50 mV s −1 to rule out any prospective contributions from capacitive current. EIS was employed to measure the Ohmic resistance of the electrocatalytic system.…”
Section: Methodsmentioning
confidence: 99%
“…38 A lack of peaks corresponding to Ru compounds was also present in the XRD pattern, which indicated that no new crystalline phases were generated during sample preparation, suggesting that the constructed P and Ru materials mainly exist in an amorphous and weakly crystalline state. [39][40][41] The Ru@P-NF electrode was further characterized by high-resolution scanning electron microscopy (HR-SEM, Fig. 1b-d).…”
Section: Synthesis and Characterization Of The Electrocatalystsmentioning
confidence: 99%